Application of Maqashid Sharia Principles In Islamic Security Crowdfunding Contracts in Indonesia - Irma Rachmawati Maruf (Jurnal Sosial Sains dan Komunikasi, 2024)
This study aims to identify the issues of maqashid sharia and the importance of supervision in implementing Islamic Security Crowdfunding (ISF) contracts. Sharia compliance regulation is an essential subsystem within the Islamic social finance ecosystem. This research is a legal study utilizing legislative and conceptual approaches. Indonesia is one of the countries with a rapidly growing Sharia financial sector. The findings on Sharia compliance regulation in ISF are a comprehensive approach to developing a sustainable Islamic social finance ecosystem. Platforms and issuers in ISF must implement Maqashid Sharia. Therefore, it is crucial to consider the requirements of Maqashid Sharia in ISF contracts.